P517 One year effectiveness and safety of ustekinumab in Ulcerative Colitis: a multicentre real-world study from Italy. (27th May 2021) - Chiappetta, M F; Viola, A; Mastronardi, M; Turchini, L; Carparellli, S; Orlando, A; Biscaglia, G; Miranda, A; Guida, L; Costantino, G; Scaldaferri, F; Bossa, F; et al.
Abstract: Background: Efficacy and safety of ustekinumab for the treatment of Ulcerative colitis (UC) has been demonstrated in phase III clinical trials, but real world data are scarce. The aim of this study was to assess effectiveness and safety of ustekinumab in an Italian cohort of UC patients. Methods: Data of patients with UC who started using ustekinumab were collected. Primary endpoint was steroid-free clinical remission at 24 and 52 weeks of therapy. Secondary endpoints were: treatment response, endoscopic remission, treatment persistence at 12 months and safety. Results: A total of 68 patients (males 63.2 %; mean age (SD) 31 years (14.5)) were included. All patients were biologics experienced. At 24 and 52 weeks, 32 % and 50 % of patients achieved steroid-free clinical remission, 85% and 81% had clinical response, respectively. (Table 1 ) At the end of follow-up there were a significant reduction of pMS from baseline (p<0.001) and of steroid use (p<0.001) (Figure 1 ). Of the available endoscopies at 12 months (18/38), 22.2% showed mucosal healing. The probability to persist in therapy with ustekinumab after 12 months of treatment was of 89.7 %. Only one adverse event occurred (diagnosis of an hypophysis adenoma). No patients required colectomy. Conclusion: Data from our small real-life cohort of treatment-refractory UC patients suggest satisfactory effectiveness of ustekinumab and an excellent safety. More data assessing mucosal healing after one year of treatment are needed